Comparative analysis of the demographic parameters of seven spotted ladybird beetle (Coleoptera: Coccinellidae) reared on various host aphid species - Farooq,Muhammad; Zhu,Xun; Shakeel,Muhammad; Iftikhar,Ayesha; Shahid,Muhammad Rafiq; Saeed,Nadia; Arain,Muhammad Shahid (PeerJ, 2020)
Background The demographic parameters of the predacious seven spotted ladybird beetle Coccinella septempunctata Linnaeus (Coleoptera: Coccinellidae) reared on the following four host aphid species were compared: Rhopalosiphum padi Linnaeus (Hemiptera: Aphididae), Rhopalosiphum maidis Fitch (Hemiptera: Aphididae), Sitobion avenae Fabricius (Hemiptera: Aphididae), and Schizaphis graminum Rondani (Hemiptera: Aphididae). Methods The developmental period, fecundity, adult preoviposition period, total preoviposition period and population parameters were evaluated based on the two-sex age-stage life table. The duration of the developmental stages and the population parameters were calculated with the TWOSEX-MSChart program, whereas population size was projected based on the two-sex age-stage life table data with the TIMING-MSChart program. Results The intrinsic rate of increase (r) was the highest in the R. padi predators (0.1946 per day), followed by the S. graminum (0.1435 per day), S. avenae (0.1400 per day), and R. maidis (0.1180 per day) predators. The differences in the net reproductive rate (R0) and the finite rate of increase (λ) when C. septempunctata was reared on the four aphid species were consistent with the r values. This trend was reversed for the mean generation time (T), which ranged from 29.02 days for the lady beetles reared on R. padi to 39.75 days for the lady beetles reared on R. maidis. Interestingly, R. padi was the most suitable host, while the congeneric R. maidis was the least suitable. The results of this study may be useful for future investigations regarding the ecological effects of predatory species and the mass-production of C. septempunctata in the laboratory for an augmentative release of an aphid predator.
Keywords: Age-stage; Aphid species; Population parameters; Two sex life table